TREM2 Overexpression Attenuates Cognitive Deficits in Experimental Models of Vascular Dementia - Qian Wang; Weixia Yang; Jingmei Zhang; Yueran Zhao; Yuzhen Xu (Neural Plasticity)
Neuroinflammation plays a prominent role in the pathogenesis of vascular dementia (VD). Triggering receptor expressed on myeloid cells 2 (TREM2) is a transmembrane receptor mainly expressed on microglia and has been known for its anti-inflammatory properties during immune response. However, data evaluating the effects of TREM2 in VD are lacking. Therefore, the present study is aimed at investigating the role of TREM2 in VD. In this study, the mouse model of VD was induced by transient bilateral common carotid artery occlusion (BCCAO). We compared the hippocampal gene and protein expressions of TREM2 between the VD mice and sham-operated mice at different time points. The TREM2 mRNA and protein expression levels in the VD mice were higher than those in the sham-operated mice. The cognitive deficits of VD mice were observed in the Morris water maze test. Interestingly, overexpression of TREM2 by intracerebroventricular injection of a lentiviral vector that encoded TREM2 (LV-TREM2) significantly improved the spatial learning and memory and attenuated the hippocampal neural loss in VD mice. Further mechanistic study revealed that overexpression of TREM2 significantly inhibited microglia M1 polarization by decreasing inducible nitric oxide synthase (iNOS) and proinflammatory cytokines expression levels and conversely enhanced microglia M2 polarization by increasing Arginase-1 (Arg-1) and anti-inflammatory cytokine expression levels. These results strongly suggest that TREM2 provides a protective effect in VD via modulating the phenotype of activated microglia and may serve as a novel potential therapeutic target for VD.